2021
DOI: 10.3390/pathogens10111419
|View full text |Cite
|
Sign up to set email alerts
|

Ascaris suum Nutrient Uptake and Metabolic Release, and Modulation of Host Intestinal Nutrient Transport by Excretory-Secretory and Cuticle Antigens In Vitro

Abstract: Ascaris suum, the most important pig parasite, also infects humans as a zoonotic pathogen. Malabsorption upon infection probably results from impaired nutrient transport, presumably mediated by the parasite’s excretory-secretory (ES) or cuticle somatic (CSO) antigens. The present study investigated the electrogenic transport (ΔIsc) of glucose, alanine and the dipeptide glycyl-l-glutamine (glygln), as well as glucose net flux rates in pig jejunal tissue after in vitro exposure to adult A. suum total ES or CSO a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 41 publications
0
8
0
2
Order By: Relevance
“…In rats, infection with the roundworm N. brasiliensis directly impaired glucose absorption in intestinal epithelial cells 119 . An in vitro study in pigs demonstrated that Ascaris suum not only directly absorbs glucose and amino acids into its own body, but also exposing porcine intestinal cells to A. suum excretory‐secretory products alone is sufficient to inhibit their absorption of glucose and alanine 120 . Intriguingly, treatment of roundworm‐infected pigs with the probiotic Bifidobacterium lactis attenuated the nutrient malabsorption induced by A. suum , 121 strongly implying that the Bifidobacterium genus has a universal beneficial effect on malnourishment.…”
Section: Child Growth Undernutrition and Stuntingmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, infection with the roundworm N. brasiliensis directly impaired glucose absorption in intestinal epithelial cells 119 . An in vitro study in pigs demonstrated that Ascaris suum not only directly absorbs glucose and amino acids into its own body, but also exposing porcine intestinal cells to A. suum excretory‐secretory products alone is sufficient to inhibit their absorption of glucose and alanine 120 . Intriguingly, treatment of roundworm‐infected pigs with the probiotic Bifidobacterium lactis attenuated the nutrient malabsorption induced by A. suum , 121 strongly implying that the Bifidobacterium genus has a universal beneficial effect on malnourishment.…”
Section: Child Growth Undernutrition and Stuntingmentioning
confidence: 99%
“…119 An in vitro study in pigs demonstrated that Ascaris suum not only directly absorbs glucose and amino acids into its own body, but also exposing porcine intestinal cells to A. suum excretory-secretory products alone is sufficient to inhibit their absorption of glucose and alanine. 120 Intriguingly, treatment of roundworm-infected pigs with the probiotic Bifidobacterium lactis attenuated the nutrient malabsorption induced by A. suum, 121 strongly implying that the Bifidobacterium genus has a universal beneficial effect on malnourishment. Further investigation of the intersectionality of helminth infection and the GM in the context of malnutrition could unveil interesting, novel and cost-effective pre/pro-biotic co-therapies in an effort to combat the morbidities associated with global undernutrition.…”
Section: Child Growth Undernutrition and Stuntingmentioning
confidence: 99%
“…For Ussing chamber experiments, intestinal segments measuring 50 cm in length were taken directly distal of the aforementioned sampling sites, rinsed with ice-cold 0.9% NaCl and stored in Ussing buffer as previously described (Koehler et al, 2021a(Koehler et al, , 2021b.…”
Section: Collection Of Pig Intestinal Mucosa Samplesmentioning
confidence: 99%
“…at the end of the pre-patent period and therefore at a time point comparable to day 49 pi for A. suum (Schwarz et al ., 2011 ). When excretory–secretory (ES) antigens of adult A. suum were added to porcine jejunal mucosa in an in vitro set-up, an immediate impairment of glucose and alanine transport was evident (Koehler et al ., 2021 b ). Therefore, adult parasites may exhibit a stronger modulatory effect on the porcine mucosa as compared to larval or pre-adult parasite stages; however, this has not been investigated yet in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a 12% reduction in live weight gain was found in A. suum-infected versus anthelminthic-treated pigs in an outdoor system [10]. Reduced feed utilization efficiency is presumably due to a parasite-induced reduction in sodium-coupled intestinal glucose resorption [11][12][13][14]; however, alterations of the intestinal microbiota might also play a role. It has been suggested that A. suum actively manipulates its microbial environment by the release of potent antimicrobial proteins and peptides, thereby creating a favourable metabolic environment and immunoregulatory state [2,15].…”
Section: Introductionmentioning
confidence: 99%